DA'WAH, SOLIDARITAS, DAN MEDIA: ANALISIS SOSIOLOGIS KOMUNIKASI PEMUDA HIZBULLAH DALAM MENDUKUNG PEMBEBASAN AL-AQSA - Rukanda Sastra Gunawan; Arif Ramdan Sulaeman; Anisa Fithri Nurjannah (Lembaga Sepercenter, 2025)
This study aims to analyse the contribution and role of the youth of Jama'ah Muslimin (Hizbullah) in supporting the liberation of Al-Aqsa Mosque, using a sociological communication approach. The main focus of the research is on the dimensions of da'wah communication, religious solidarity, and the use of media as a means of mobilising support for the Palestinian issue. Specifically, this research seeks to prove: (1) the tangible contribution of the youth of Jama'ah Muslimin (Hizbullah); and (2) the existence of their role in the movement to defend Al-Aqsa Mosque. This research was conducted on 48 young members of the Jama’ah Muslimin (Hizbullah) in the JABODETABEK region. The method used was a descriptive qualitative approach, with data analysis techniques including observation, interviews, and documentation. The results of the study indicate that there is a significant contribution through da'wah activities, solidarity campaigns, and the use of social media as a tool for spreading the narrative of liberation. Additionally, their role in the struggle is evident in the form of public advocacy, the organisation of solidarity actions, and the strengthening of Islamic identity integrated with geopolitical awareness. These findings reinforce the position of Hizbullah youth as social actors in transnational religious movements through strategic communication approaches.